The walk on - Feinstein, John. (2014)
After moving to a new town his freshman year in high school, Alex Myers is happy to win a spot on the varsity team as a quarterback but must deal with idea of not playing for two years since the first-string quarterback is not only a local hero, he is also son of the corrupt head coach.
Keywords: Football -- Fiction; Coaches (Athletics) -- Fiction; High schools -- Fiction; Schools -- Fiction; Moving (Households) -- Fiction; Divorce -- Fiction